23:1 Bandwidth ratio quasi‐lumped component balun on a multilayer organic substrate. Issue 5 (1st April 2016) - Pham, Binh L.; Ta, Hai H.; Pham, Anh‐Vu; Leoni, Robert E.; Leviatan, Yehuda
Abstract : In this study, the authors present the design and development of a novel ultra‐wideband coupled‐line balun on a multilayer liquid crystal polymer substrate. The balun is designed using a quarter wavelength ( λ /4) asymmetric broadside coupled line. The defected ground structure and a lumped phase compensation circuit are developed to achieve wide bandwidth performance for the balun. The balun has a measured bandwidth ratio of 23:1, from 80 to 1860 MHz. Within the operating bandwidth, the experimental results demonstrate that the balun achieves an input return loss of better than 10 dB, an insertion loss of better than 1 dB, an amplitude imbalance of better than ±0.4 dB and a phase imbalance of better than ±10°. The size of the balun is 40.64 mm × 40.64 mm or 0.22 λ g × 0.22 λ g, where λ g is the guided wavelength at the centre frequency of 970 MHz.